The diffusion of accounting reform in Sri Lanka: an analysis of two layers of diffusion among three levels of government. Issue 8 (12th April 2021) - Dissanayake, Thusitha; Dellaportas, Steven; Yapa, Prem W.S.
Abstract : Purpose: The purpose of this study is to evaluate the implementation of accrual accounting among two layers of government in Sri Lanka. This study examines the process of diffusion and application among and between provincial governments and local governments to assess the barriers and enablers on the implementation of accrual accounting. Design/methodology/approach: The study relies on data collected through interviews with 30 accounting and finance personnel from all levels of government active in the diffusion process. Interviews were conducted to gather and assess their insights and perceptions on the diffusion of accrual accounting. The data are examined initially using Rogers (1995) "diffusion of innovation" theory to explain the factors influencing the diffusion and adoption of accrual accounting at two levels of government but the analysed primarily by comparing the perspectives of respondents between the different layers of government. Findings: The findings show that the adoption of accrual accounting was more effective among local governments compared with provincial governments. The lack of effective communication and engagement from the leaders of the innovation failed to persuade provincial government adopters of the true value of the accounting reform. This is contrasted with local governments who openly adopted accrual accounting but not in response to pressure from provincial government, who have oversight responsibility for local governments, but in response to funding protocols initiated by the central government to account for grant funding. Research limitations/implications: The findings of the study should be interpreted with caution as the data are obtained from the narrow cohort of accounting and finance professionals and may not reflect the views or experience of all stakeholders involved in the diffusion of accrual accounting. Originality/value: The paper contributes to the diffusion of accounting innovation literature by examining the role of key players in different layers of government, particularly visible among provincial governments where the lack of engagement delayed its commitment to the implementation of accrual accounting.